Interplay of electronic and magnetic phase modulation in a spin-polarised nanomagnet - Subhasmita Kar; Neelam Gupta; Debangsu Roy; Soumya Jyoti Ray (Scientific Reports)
Abstract The 2H-phase of monolayer vanadium diselenide (VSe $$_2$$ ) has recently emerged as a very intriguing material in spintronics due to its intrinsic ferromagnetism with semiconducting properties. In the present work, first-principles based calculations have been employed to systematically study the electronic, magnetic, and optical behaviour of 2D VSe $$_2$$ for investigating the impact of different external excitations such as strain, electric field, and pressure on the material. Specifically, the magnetic moment, band gap, Curie temperature (T $$_c$$ ), and absorption coefficient could be modulated, as the states near the Fermi level are mainly contributed by the in-plane atomic orbitals. The presence of different electronic phases in 2D VSe $$_2$$ can be modulated from semiconductor to half-metal and even normal metal under the influence of external stimuli. Furthermore, the in-plane biaxial strain can effectively tune the T $$_c$$ and attains a maximum value of 354K at $$η _b$$ = 6%. The maximum observed absorption coefficient is found to be 5.05 $$×$$ 10 $$^5$$ cm $$^{-1}$$ (at 1.4 eV) under the applied pressure of 30 GPa, indicating that the VSe $$_2$$ exhibits strong light absorption in the visible region. The unique combination of electronic phases, robust ferromagnetism, and optical activity makes the 2H-VSe $$_2$$ a suitable candidate for flexible electronic, optoelectronic, and spintronic applications.